An appraisal of naming patterns for school with reference to Dzumeri Community in Mopani District, Limpopo Province, South Africa - Mabunda, Philadelphia Nomayanga (My University, 2012)
The purpose of this study is to investigate and examine the naming patterns of schools among the people of Dzumeri community, in Mopani District, Limpopo Province. The study demonstrates the importance of naming and the patterns when naming a school. The study also reveals that there are schools named after the royal family, nick-names, and natural features and after an occurrence of events. In the end, the recommendations were suggested for the naming of schools. This will help in coming up with school names that will be accepted by all.
Thesis (M.A. (African Languages)) -- University of Limpopo, 2012
Keywords: Schools naming; Names, African; Schools -- Names